2017
DOI: 10.1155/2017/7284872
|View full text |Cite
|
Sign up to set email alerts
|

Tumorigenic and Differentiation Potentials of Embryonic Stem Cells Depend on TGFβFamily Signaling: Lessons from Teratocarcinoma Cells Stimulated to Differentiate with Retinoic Acid

Abstract: A significant challenge for the development of safe pluripotent stem cell-based therapies is the incomplete in vitro differentiation of the pluripotent stem cells and the presence of residual undifferentiated cells initiating teratoma development after transplantation in recipients. To understand the mechanisms of incomplete differentiation, a comparative study of retinoic acid-induced differentiation of mouse embryonic stem (ES) and teratocarcinoma (EC) cells was conducted. The present study identified differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…The differentiation potential of the pluripotent stem cells, ESCs R1 and EGCs-10, and teratocarcinoma cells, ECCs F9 and ECCs P19, was significantly different during spontaneous in vitro differentiation and after transplantation into Nude mice [4648]. However, during RA-induced differentiation, the ESCs, EGCs and ECCs exhibited similar, nearly two-fold decreases in the number of cells in the S-phase of the cell cycle (30–40%) and the number of Oct4-expressing cells (50–60%) (Figure 2A–2C).…”
Section: Resultsmentioning
confidence: 99%
“…The differentiation potential of the pluripotent stem cells, ESCs R1 and EGCs-10, and teratocarcinoma cells, ECCs F9 and ECCs P19, was significantly different during spontaneous in vitro differentiation and after transplantation into Nude mice [4648]. However, during RA-induced differentiation, the ESCs, EGCs and ECCs exhibited similar, nearly two-fold decreases in the number of cells in the S-phase of the cell cycle (30–40%) and the number of Oct4-expressing cells (50–60%) (Figure 2A–2C).…”
Section: Resultsmentioning
confidence: 99%
“…The authors concluded that the tested AuNPs did not markedly alter the in vitro differentiation potentials of hESCs [ 88 ]. Gordeeva and Khaydukov [ 91 ] explored the mechanisms of incomplete differentiation in a comparative study of RA-induced differentiation of mouse ESCs and teratocarcinoma (EC) cells. Higher expression of Nanog , Mvh , Activin A , and BMP4 were evident in undifferentiated ESCs compared to EC cells.…”
Section: Resultsmentioning
confidence: 99%
“…[ 103,105,107 ] Successful clinical use of hPSC therapies is likely to require that most, if not all, neural cells of interest be differentiated beyond the hPSC stage since residual hPSCs could produce teratoma tumors if transplanted into the patient. [ 108 ] This is a serious safety issue for hPSC-based therapies. Since our hPSC derived lines of hNP cells are devoid of pluripotent cells and recent successful animal models of stroke indicate a benefi t, we, as well as others, are motivated to conduct further translational research.…”
Section: Human Stem Cellsmentioning
confidence: 99%